Essential Role of σ Factor RpoF in Flagellar Biosynthesis and Flagella-Mediated Motility of Acidithiobacillus caldus - Yang, Chun-Long; Chen, Xian-Ke; Wang, Rui; Lin, Jian-Qiang; Liu, Xiang-Mei; Pang, Xin; Zhang, Cheng-Jia; Lin, Jian-Qun; Chen, Lin-Xu (Frontiers in Microbiology, 2019)
Acidithiobacillaceae, an important family of acidophilic and chemoautotrophic sulfur or iron oxidizers, participate in geobiochemical circulation of the elements and drive the release of heavy metals in mining associated habitats. Because of their environmental adaptability and energy metabolic systems, Acidithiobacillus spp. have become the dominant bacteria used in bioleaching for heavy metal recovery. Flagella-driven motility is associated with bacterial chemotaxis and bacterial responses to environmental stimuli. However, little is known about how the flagellum of Acidthiobacillus spp. is regulated and how the flagellum affects the growth of these chemoautotrophic bacteria. In this study, we analyzed the flagellar gene clusters in Acidithiobacillus strains and uncovered the close relationship between flagella and the sulfur-oxidizing systems (Sox system). The σ28 gene (rpoF) knockout and overexpression strains of Acidithiobacillus caldus were constructed. Scanning electron microscopy shows that A. caldus ΔrpoF cells lacked flagella, indicating the essential role of RpoF in regulating flagella synthesis in these chemoautotrophic bacteria. Motility analysis suggests that the deletion of rpoF resulted in the reduction of swarming capability, while this capability was enhanced in the rpoF overexpression strain. Both static cultivation and low concentration of energy substrates (elemental sulfur or tetrathionate) led to weak growth of A. caldus ΔrpoF cells. The deletion of rpoF promoted bacterial attachment to the surface of elemental sulfur in static cultivation. The absence of RpoF caused an obvious change in transcription profile, including genes in flagellar cluster and those involved in biofilm formation. These results provide an understanding on the regulation of flagellar hierarchy and the flagellar function in these sulfur or iron oxidizers.